1981
DOI: 10.1111/j.1432-1033.1981.tb05582.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoaffinity Labeling of Steroid Binding Proteins with Unmodified Ligands

Abstract: Photoactivation of the a,/?-unsaturated ketones of natural and synthetic steroid molecules by light of 2 2 330 nm allows their covalent attachment to steroid-binding proteins. The general validity of this method is demonstrated with two steroid hormone receptors and the steroid-binding protein uteroglobin. Progesterone can be covalently attached to the partially purified progesterone receptor and to uteroglobin, and comigrates with the binding proteins upon electrophoresis in polyacrylamide gels containing sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1982
1982
1991
1991

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…Similar difficulties have also been documented for other steroid receptor systems [13,14]. However, it has been found that steroid ligands, which contain a conjugated diene-one functional group, are generally more photoreactive [14,15]. This enhanced photoreactivity can be attributed partially to the fact that the absorption maximum of the conjugated diene-one system is -300 nm.…”
Section: Purification Of the Ecdysteroid Receptors In Drosophila K Csupporting
confidence: 63%
“…Similar difficulties have also been documented for other steroid receptor systems [13,14]. However, it has been found that steroid ligands, which contain a conjugated diene-one functional group, are generally more photoreactive [14,15]. This enhanced photoreactivity can be attributed partially to the fact that the absorption maximum of the conjugated diene-one system is -300 nm.…”
Section: Purification Of the Ecdysteroid Receptors In Drosophila K Csupporting
confidence: 63%
“…The 90,000-M, form of the glucocorticoid receptor was purified from rat liver cytosol in the activated form (7). The receptor preparations used for these studies were on average 60% pure, as judged by silver staining of sodium dodecyl sulfate-polyacrylamide gels (20) and photoaffinity labeling (40).…”
Section: Methodsmentioning
confidence: 99%
“…Identification of the receptor bands was performed by photoaffinity labeling with radioactive ligand followed by fluorography (9,10).…”
Section: Methodsmentioning
confidence: 99%